Research Progress of Silicon Suboxide-Based Anodes for Lithium-Ion Batteries - Zhou, Xiaozhong; Qi, Zhaoyi; Liu, Qiang; Tian, Jibin; Liu, Mingxia; Dong, Kaifa; Lei, Ziqiang (Frontiers in Materials, 2021)
With unique advantages, such as high energy density, long lifespan and environmental friendliness, lithium-ion batteries (LIBs) have been widely used in various portable electronics, and placed great expectations on the application in electric vehicles. To meet the ever-increasing high-energy-density demand of the next-generation LIBs, silicon suboxide SiOx(0 < x < 2) has been considered as one of the most promising anode materials, due to its high mass specific capacity, good cycling performance, proper working potential, low cost, and environmental friendliness. However, there are still several drawbacks before the application of SiOx, such as low intrinsic electronic conductivity and high irreversible capacity in the first cycle, which lead to low electrochemical activity and low initial coulombic efficiency (ICE). To tackle these issues, extensive efforts have been made and remarkable progresses have achieved in recent years. Here, latest developments of SiOx-based anodes are briefly reviewed, especially on the subject of metal/metal oxide doping on SiOx-based electrode materials, and the future application of SiOx anodes in rechargeable LIBs is also prospected.